PENERAPAN E-COMMERCE SEBAGAI MEDIA PENJUALAN ONLINE (STUDI KASUS PADA TOKO SINAR TERANG BANDAR LAMPUNG) - Ulfa Fitriyani Yapan (Jurnal Multimedia dan Android (JMA), 2022)
E-Commerce Implemention as Media Online Sales ( Case Study on Sinar Terang Store Bandar Lampung).This research took a title of E-Commerce Implemention as Media Online sales. The purpose in this research is implements the e-commerce website which serves as a promotion media and electronic sales. And to know what’s problems be faced in implementation of e-commerce website.This kind of this research is qualitative research. This reserach took a case study on Sinar Terang Store in Bandar Lampung. The source of the data obtained by primary data and secondary data source. The data collection technique in this research use observation, interviewand documentation.The research result use e-commerce implementation with opencart software on Sinar Terang storein Bandar Lampung will be able to help reduce cost and can convey information in detail and quickly about this product to consumen. Based on research result be expected to help Sinar Terang store for receive a good profit and can compere with similar stores